Factorial screening of platinum removal using flat sheet supported liquid membrane - Siti Masyitah, Mokhtar; Rajendaren, Vikneswary; Syed Mohd Saufi, Tuan Chik; Norasikin Syahmi Izzati, Othman Ali; Raja Norimie, Raja Sulaiman (Desalination Publications, 2022)
Excessive platinum (Pt) discharged into the environment from industrial wastewater must be effectively treated since it contaminates the environment and causes substantial environmental problems and severe health risks to humans. Flat sheet supported liquid membrane (FSSLM) was used to remove Pt from an aqueous solution using liquid membrane formulated from Aliquat 336 carrier in kerosene. Fractional factorial design (FFD) was applied to screen five FSSLM operation parameters, including the Aliquat 336 carrier concentration (factor A), Pt feed phase concentration (factor B), sodium perchlorate stripping phase concentration (factor C), feed flow rate (factor D) and stripping phase flow rate (factor E). The percentage of Pt removal from an aqueous solution was the response in the FFD. The feed flow rate (factor D) was the most significant main factor to the FSSLM performance, with 25.02% of the contribution. The interaction between factor AC and factor BE induced the most significant effect with 26.95% and 12.14% of the contribution, respec-tively. The highest removal percentage for Pt via the FSSLM process was 98.7% using 0.5 M Aliquat 336 concentration, 5 mg/L feed concentration, 0.5 M stripping concentration, 100 mL/min feed flow rate, and 50 mL/min stripping flow rate.